Pengaruh Pengangguran Terhadap Iklim Investasi Syariah Di Provinsi Jambi - Maulana Farhan; Ary Dean Amry (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Unemployment is someone in the labor force category who does not find work. Based on data from BPS regarding the number of unemployed people in Jambi Regency / Province in 2021 of 10.6 percent, it shows that sharia investment in Jambi City is still very relatively low. The purpose of this study to be achieved is to find out and analyze how the effect of unemployment on the Islamic investment climate in Jambi Province. This research using quantitative methods was conducted in time series from 2011 to 2022. From the data obtained, 59% of the sharia investment climate index in Jambi Province is influenced by the population growth rate. Showing that unemployment does not affect the lack of Islamic investment, because the ethical level of the Islamic investment climate increased by 1%, the unemployment rate decreased by 1.55, which certainly has a very positive impact on the Islamic investment climate. Efforts are needed to increase the value of the Sharia Investment Climate Index, with the hope that human progress will continue to develop.